2015
DOI: 10.1007/s00284-015-0872-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for the Spread of Serratia marcescens Within Dental-Unit Waterline Systems Using Vermamoeba vermiformis

Abstract: (2015) Risk assessment for the spread of Serratia marcescens within dental unit waterline systems using Vermamoeba vermiformis. Current Microbiology, 71 (4). pp. 434 442.It is advisable to refer to the publisher's version if you intend to cite from the work.http://dx.doi.org/10.1007/s00284-015-0872-0For more information about UCLan's research in this area go to http://www.uclan.ac.uk/researchgroups/ and search for . Conflict of interest disclosure statementAll named authors declare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 53 publications
1
15
0
11
Order By: Relevance
“…The large size of the L. pneumophila seen under the electron microscope also supports this conclusion, as it was out-with the size-range of bacteria, this amoeba choose to feed upon (Dillon et al 2014 b ;Lal et al 2015).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The large size of the L. pneumophila seen under the electron microscope also supports this conclusion, as it was out-with the size-range of bacteria, this amoeba choose to feed upon (Dillon et al 2014 b ;Lal et al 2015).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, the rationale for sub-culturing all colonies that were initially observed on GVPC plates was to determine whether they were Legionella, as a variety of non-Legionella species with glassy appearance, a typical example S. marcescens, can also grow on this medium (Lal et al 2015). By culturing bacteria on R2A, the isolated bacteria may demonstrate their pigmentation and swarming characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations